Strategi Inovasi untuk Meningkatkan Value pada Industri Jasa Pendidikan dalam Memenuhi Customer Satisfaction - Emmy Nurhayati (Universitas Sarjanawiyata Tamansiswa, 2021)
The current Covid-19 pandemic has forced the education service industry to change learning patterns. Various problems arise when the learning method is carried out. This study aims to create an innovative strategy in increasing value to meet customer satisfaction through the learning method carried out as well as things that need to be improved to maintain the quality of learning outcomes. The object of research is the perception of students of Industrial Engineering Program at XYZ University towards learning methods. The methods used in this study are the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods based on questionnaires distributed to consumers. The results of this study showed that students' perceptions of the learning method based on the CSI is Satisfied with a percentage of 72,76% and the results of IPA showed Good results with a percentage of 80,21%. The innovation strategy created for system development that seeks to design strategies to increase value through the quality of learning for students with learning methods during the Covid-19 pandemic in meeting customer satisfaction.